2020
DOI: 10.21203/rs.3.rs-26481/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Birth weight and renal markers in children aged 5 – 10 years in Cameroon: A cross-sectional study

Abstract: Background A relationship exists between birth weight (BW) and glomerular filtration rate (GFR) in postnatal kidney. Willing to fill a gap of knowledge in sub-Saharan Africa, we assessed the effect of BW on blood pressure (BP), proteinuria and GFR among Cameroonians children.Methods This was a cross-sectional hospital-based study from January to April 2018 at the Yaounde Gynaeco-Obstetric and Paediatric Hospital (YGOPH). We recruited low BW (LBW) [<2500g], normal BW (NBW) [2500-3999g] and high BW (HBW) [>… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…The authors suggested that proteinuria seen in these patients was caused by glomerular hypertension and GHF [145]. Similar investigation by Kaze et al reported significant proteinuria in children with LBW in comparison with those with NBW and related this finding to GHF theory [141]. b.…”
Section: Factors Modulating the Development Of Ghfmentioning
confidence: 53%
See 1 more Smart Citation
“…The authors suggested that proteinuria seen in these patients was caused by glomerular hypertension and GHF [145]. Similar investigation by Kaze et al reported significant proteinuria in children with LBW in comparison with those with NBW and related this finding to GHF theory [141]. b.…”
Section: Factors Modulating the Development Of Ghfmentioning
confidence: 53%
“…More so, Kaze et al investigated the relationship between birth weight and eGFR in 80 children aged 5-10 years. These authors found a trend towards an increased eGFR (eGFR ≥ 120 mL/min/1.73 m 2 ), although not statistically significant, in children with LBW when compared with children with normal birth weight (NBW) [141].…”
Section: Factors Modulating the Development Of Ghfmentioning
confidence: 89%